A managed alcohol program in Sydney, Australia: Acceptability, cost‐savings and non‐beverage alcohol use. (17th April 2018) - Ezard, Nadine; Cecilio, Michael E.; Clifford, Brendan; Baldry, Eileen; Burns, Lucinda; Day, Carolyn A.; Shanahan, Marian; Dolan, Kate
Abstract: Introduction and Aims: Managed alcohol programs (MAPs) are a novel harm reduction intervention for people who experience long‐term homelessness and severe long‐term alcohol dependence. MAPs provide regulated amounts of alcohol onsite under supervision. Preliminary international evidence suggests that MAPs are associated with improvements such as reduced non‐beverage alcohol consumption and decreases in some alcohol‐related harms. There are currently no MAPs in Australia. We aimed to assess the feasibility of a MAP in inner‐Sydney. Design and Methods: A survey among eligible homeless alcohol‐dependent residents of an inner‐Sydney short‐stay alcohol withdrawal service occurred in 2014 to assess acceptability. Administrative data were analysed to ascertain estimates of cost‐savings for a MAP based in Sydney. Results: Fifty‐one eligible participants were surveyed. More than one‐quarter (28%) reported consumption of non‐beverage alcohol. A residential model received greatest support (76%); the majority (75%) of participants indicated a willingness to pay at least 25% of their income to utilise a MAP. Hospital and crisis accommodation cost‐savings were conservatively estimated at AUD926 483.40 and AUD347 574.00, respectively per year for a 15‐person residential MAP. Discussion and Conclusions: Our findings demonstrate the acceptability of a MAP in Sydney among a target population sample, with the implementation of a residential MAP likely to produce significant cost‐savings. A trial of a Sydney MAP evaluating the impact on health and social outcomes, including a comprehensive economic evaluation, is strongly recommended.